Cloud computing with e-science applications - Terzo, Olivier; Mossucca, Lorenzo (Boca Raton : CRC Press, Taylor & Francis Group, 2015)
"The amount of data in everyday life has been exploding. This data increase has been especially significant in scientific fields, where substantial amounts of data must be captured, communicated, aggregated, stored, and analyzed. This book describes how cloud computing can significantly improve data management in different scientific fields, such as bioinformatics, earth science, and computer science. This book focuses on how cloud computing helps in the areas of resource control, vertical and horizontal scalability, and adaptive scheduling"--
computer bookfair2016
Includes bibliographical references and index.
Keywords: Research -- Data processing; Science -- Data processing; Cloud computing; COMPUTERS / Internet / General; MATHEMATICS / General; TECHNOLOGY & ENGINEERING / Electrical